Levi Strauss & Co. : driving adoption of green chemistry - Strand, Robert, (SAGE Knowledge. Cases., 2017)
This case examines the challenges and opportunities faced by Levi Strauss & Co. (LS&Co.) as it attempts to help establish a cross-industry sustainability initiative to eliminate hazardous chemicals in the apparel supply chain. LS&Co.s Screened Chemistry Program screened chemical formulations against human and environmental health hazard endpoints before they chemicals entered the supply chain. This shift represents a radical departure from the status quo that requires widespread collaboration across the industry to implement. This case explores the associated challenges and opportunities to achieve cross-industry collaboration to achieve a sustainability objective.